The Role of Tertiary Institutions in Increasing Understanding of The Protection of Child Abuse Laws in Communities in Sukabumi - R.Eriska Ginalita Dwi Putri; Haidan Angga Kusumah; Asti Sri Mulyanti (ADI Publisher, 2020)
Violence against children can always occur in situations and conditions at any time and thing this can be caused by conflicts that occur both within the family and community environment. In the family sphere, conflicts usually occur within the household committed by husbands and wives whose effects can lead to an outlet of violence against children that have a negative impact on physical, psychological, mental, which contrary to Law No. 35 of 2014 concerning Child Protection. 1 Likewise, in the community environment, problems often arise violence against children as a result of wrong relationships and the environment of that society itself which is not good, which is done by irresponsible people, namely sexual violence against children. So it needs protection by the state and society, which aims to provide a sense of security to children as victims as well as crack down on the culprit. Higher education as an institution that can spread values the value of kindness and understanding of the enforcement of cases of child abuse and also from the college will produce human resources who have competence to handle cases of child abuse, as well as being able to provide input and improvement of laws and regulations and policies relating to legal protection for children who are victims of violence.